Answer:
Step-by-step explanation:
General form of equation of a circle is expressed as [tex](x-a)^{2} + (y-b)^{2} =r^{2}[/tex] where r is the radius of the circle and (a, b) is the center of the circle.
Given the equation of a circle to be [tex](x-20)^{2}+(y-0.05)^{2} = 81[/tex], rewriting the equation to conform to the general equation above we have;
[tex](x-20)^{2}+(y-0.05)^{2} = 9^{2}[/tex]
Comparing the equation given to the general equation above, a = 20, b = 0.05 and the radius of the circle will be 9. The center (a, b) will be (20, 0.05).